Biochemical and Radical-Scavenging Properties of Sea Cucumber (Stichopus vastus) Collagen Hydrolysates - Karim, Md. Rezaul; Md. Zainul, Abedin; Alias, A. Karim; Aishah, A. Latiff; Chee, Yuen Gan; Farid, Che Ghazali; Zoha, Barzideh; Sahena, Ferdosh; Md Jahurul Haque, Akanda; Wahidu, Zzaman; Md. Zaidul Islam, Sarker (Taylor & Francis, 2014)
The molecular mass distribution, amino acid composition and radical-scavenging activity of collagen hydrolysates prepared from collagen isolated from the sea cucumber Stichopus vastus were investigated. β and α1 chains of the collagen were successfully hydrolysed by trypsin. The molecular mass distribution of the hydrolysates ranged from 5 to 25 kDa, and they were rich in glycine, alanine, glutamate, proline and hydroxyproline residues. The hydrolysates exhibited excellent radical-scavenging activity. These results indicate that collagen hydrolysates from S. vastus can be used as a functional ingredient in food and nutraceutical products.